2015
DOI: 10.1080/14649365.2015.1089586
|View full text |Cite
|
Sign up to set email alerts
|

The complex landscape of contemporary fathering in the UK

Abstract: Distinguishing between fatherhood as a social construction and fathering as a social practice, this paper presents empirical evidence from the UK concerning the complex landscape of contemporary fathering. The paper focuses on the spatial and temporal dynamics of fathering, particularly following moments of rupture and transition such as family break-up or bereavement. Based on narrative interviews and ethnographic observation, including the co-production and analysis of video data, the paper identifies three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As our familiarity with these methods and awareness of the possibilities they afford increased over time, some participants in the FOCAS study were offered the opportunity of keeping self-directed video diaries. Our use of this method in a previous study (Meah and Jackson, 2016) revealed that handing over control of the camera meant that what we saw of the household was not restricted to particular 'snapshots' when a researcher could be present. Indeed, a much more nuanced picture of household practices emerged over the space of a week or more, enabling us to better understand the motivations behind individuals' practices, as well as how cooking and eating are fitted into the exigencies of everyday life (cf.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…As our familiarity with these methods and awareness of the possibilities they afford increased over time, some participants in the FOCAS study were offered the opportunity of keeping self-directed video diaries. Our use of this method in a previous study (Meah and Jackson, 2016) revealed that handing over control of the camera meant that what we saw of the household was not restricted to particular 'snapshots' when a researcher could be present. Indeed, a much more nuanced picture of household practices emerged over the space of a week or more, enabling us to better understand the motivations behind individuals' practices, as well as how cooking and eating are fitted into the exigencies of everyday life (cf.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…This was often framed in terms of making the prospect of becoming parents more “real” and exciting for both partners. However, the use of apps as technologies for bonding work was also strongly differentiated through accounts of the significance of women's physical experience and men's lack of physical experience of pregnancy for future relations with the baby, and the implications of this for the contemporary ideal of shared parenting and involved fatherhood (Boyer et al., 2017; Meah & Jackson, 2016). To different degrees, women espoused models of active and engaged fatherhood, and expressed hopes for a future of effective co‐parenting in which they equitably shared in childcare as well as loving closeness to each other and their child.…”
Section: Togetherness and The Making Of Parentsmentioning
confidence: 99%
“…The relative invisibility, within the literature, of men's increasing involvement in family care-giving (and feeding the family specifically) is attributable to its feminisation (England and Dyck 2014), prompting an appeal for 'more sensitive readings of masculinities and caregiving' (ibid., 292). Men's roles as fathers is one example of this, with scholarship increasingly distinguishing between 'fatherhood', as a social construction, and 'fathering', as a series of social practices performed by individuals who may or may not be biologically related to a child (Meah and Jackson 2016). While some have drawn attention to the emergence of more intimate forms of involved fathering (Aitken 2005;Dermott 2009) and the 'awkward' spaces in which the daily emotional practices that constitute fathering are negotiated and contested (Aitken 2005), it is consistently recognised that fathering is a relational practice.…”
Section: Fathers Food and Carementioning
confidence: 99%
“…While some have drawn attention to the emergence of more intimate forms of involved fathering (Aitken 2005;Dermott 2009) and the 'awkward' spaces in which the daily emotional practices that constitute fathering are negotiated and contested (Aitken 2005), it is consistently recognised that fathering is a relational practice. On the one hand, contemporary fathering practices are recognised as evolving from men's own experiences of being fathered (Olmstead et al 2009;Meah and Jackson 2016); on the other hand, they continue to be constituted 'in parallel or in opposition to' those of mothers (Aitken 2000, 585; for a discussion of this, see Meah and Jackson 2016).…”
Section: Fathers Food and Carementioning
confidence: 99%